ANALISIS PEMBEBANAN BIAYA OVERHEAD PABRIK BERDASARKAN METODE ACTIVITY BASED COSTING PADA PERUSAHAAN BULUKUMBA JAYA KENDARI - Suhardi, Sri Pratiwi (JURNAL AKUNTANSI, 2016)
This research aimed to knows the imposition of overhead costs more accurately beetween the convensional methods used by Bulukumba Jaya Kendari Company and activity based costing method. While the benefits of this research is to provide input in selecting a charging method is more accurate and compatible with the conditions of the company, and as an additional reference for the development of science particularly relevant to this study.The result of this study indicate that the calculation of production costs for both types of produtcs with the cost of production based on the conventional method for adobe productsÂ  Rp 245.506.950,- and pavin block Rp 259.412.975,- and whereas adobe production costs based on activity based costing for Rp Rp 246.446.750,- and pavin block products Rp 252.066.051,- In this case there are differences in the calculation of production costs. The differences occurs because the imposition of overhead factory on each product. Imposition of costs to products based on activity based costing has described the actual costs of consumption. This is caused because of the cost drivers are used so that the resulting cost information is considered more accurate, so that give a good impact in terms of setting the selling price for expected profit.Â Keywords: The Imposition of Factory Overhead Cost, Activity Based Costing Method.